The determinants of banking sector performance in Tanzania: A pre-post Treasury Single Account analysis - Goodhope Hance Mkaro; Lin Sea Lau; Chee Keong Choong (Cogent Economics & Finance, 2023)
This study examined how the Treasury Single Account (TSA) policy, aimed at withdrawing government deposits from commercial banks, impacted the Tanzanian banking sector's performance in relation to ownership concentration, bank size, and macroeconomic variables. Balanced panel dataset comprising thirty (30) banks, from 2010Q1 to 2020Q4, was analyzed. Regression results revealed that, while foreign and state-owned banks were more resilient, private and domestic banks' performance deteriorated after TSA adoption. Small banks survived the negative TSA shock while the performance of the larger ones was negatively affected. The effects of interest rate, GDP, and exchange rate turned negative whilst the inflationary effects on bank performance were enhanced after TSA. The study enhances comprehension of the relatively new TSA system in Africa while addressing a literature gap by exploring its influence on banking sector's performance across various bank classifications. Following TSA adoption, regulators should strike a balance between tightening or relaxing regulatory limits while enforcing banks' compliance to ensure the sector's stability. Government support for key economic growth-driving sectors potentially attracts more deposits into the banking system, thus promoting the sector's stability. Banks are encouraged to innovate strategies to attract deposits from the general public, while deviating from dependence on government funds.
Keywords: 330; bank performance; ownership concentration; size; Tanzania; treasury single account